Evaluation of subclinical atherosclerosis by ultrasound radiofrequency data technology in patients with psoriatic arthritis - Ozisler,Cem (2022)
SUMMARY OBJECTIVE: This study aimed to assess the presence of subclinical atherosclerosis in patients with psoriatic arthritis using ultrasound radiofrequency data technology. METHODS: In all, 29 psoriatic arthritis patients and 42 age- and sex-matched healthy controls were included in this cross-sectional study. Arterial stiffness and carotid intima-media thickness measurements were performed in bilateral common carotid arteries using ultrasound radiofrequency data technology in all participants. RESULTS: In psoriatic arthritis patients, the mean carotid intima-media thickness, α and β stiffness indices, and pulsed wave velocity value were significantly higher than those in the control group (542.3 (81.3) vs. 487.9 (64.1), 9.3 (6.3) vs. 3.9 (0.1), 18.7 (17.7) vs. 8.04 (4.2), and 10.2 (3.8) vs. 6.4 (1.5), p<0.05). The mean distensibility coefficient and compliance coefficient values of the patient group were significantly lower than those of the control group (0.014 (0.01) vs. 0.03 (0.01) and 0.57 (0.33) vs. 1.02 (0.4), p<0.05). No significant correlation was found between carotid artery hemodynamic parameters and symptom duration, duration of diagnosis and treatment, disease activity ındex for psoriatic arthritis scores, erythrocyte sedimentation rate, and C-reactive protein levels (p>0.05). CONCLUSION: In the results of our study, evidence of subclinical atherosclerosis has been detected in psoriatic arthritis patients without clinically evident cardiovascular disease or traditional cardiovascular risk factors.